Construction géopolitique pour le développement durable d'une enclave métropolitaine du MERCOSUR - Diana Arellano; Carla Cossi (Confins)
The work proposes a diachronic analysis of the advances and setbacks in the geopolitical construction of the Binational Metropolitan Area, which makes up the cities of Posadas, Garupá and Candelaria (belonging to the province of Misiones, in Argentina) and Encarnación, Cambyretá and San Juan del Paraná (belonging to the Itapúa department, in Paraguay) as a subnational cross-border urban enclave of Mercosur. From an anthropological perspective, we seek to advance a characterization of the explanations that support the persistent vocation for integration in this metaphorically kaleidoscopic territoriality; understanding the particular reality of these border cities, which due to their geographical and urban contiguity were grouped into a study unit, which combines multiple local practices, which mix, overlap, oppose, contradict and exclude each other, beyond the state political limits that divide them. To do this, the experience of the inhabitants of this territory is investigated, who through their multi-scalar interactions of varied extension and scope; They make the cross-border enclave stand out for its heterogeneity, complexity and dynamism. regional integration, binational metropolization, cross-border territories.